2019
DOI: 10.3390/w11071442
|View full text |Cite
|
Sign up to set email alerts
|

Crushed Autoclaved Aerated Concrete (CAAC), a Potential Reactive Filter Medium for Enhancing Phosphorus Removal in Nature-Based Solutions—Preliminary Batch Studies

Abstract: Phosphorus (P) is a limited resource and can promote eutrophication of water streams and acidification of oceans when discharged. Crushed autoclaved aerated concrete (CAAC), a by-product from demolition, has shown great potential for recovering P. The potential of CAAC to be used in nature-based solutions as a P-reactive filter medium was evaluated by performing preliminary batch essays. Here, we evaluated the interactions and main effects of the initial concentration of P (Pi; 5, 10 or 20 mg L−1), particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
1
2
1
4
Order By: Relevance
“…The results showed that the P concentration in the water significantly affects the P adsorption capacity of the aerated concrete. This finding is consistent with those of previous studies (Deng & Wheatley 2018;Zhang & Zhu 2018;Castellar et al 2019). Cucarella and Renman (2009) emphasised that high solute concentrations encourage other adsorption mechanisms, such as substantial boundary concentrations; Zhang highlighted that the P adsorption of a filler is only attributed to the physical adsorption in low P concentration water, while the high P concentration of the water can sufficiently cause chemical reactions, such as complexation and precipitation, with the metals (Zhang et al 2005).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The results showed that the P concentration in the water significantly affects the P adsorption capacity of the aerated concrete. This finding is consistent with those of previous studies (Deng & Wheatley 2018;Zhang & Zhu 2018;Castellar et al 2019). Cucarella and Renman (2009) emphasised that high solute concentrations encourage other adsorption mechanisms, such as substantial boundary concentrations; Zhang highlighted that the P adsorption of a filler is only attributed to the physical adsorption in low P concentration water, while the high P concentration of the water can sufficiently cause chemical reactions, such as complexation and precipitation, with the metals (Zhang et al 2005).…”
Section: Resultssupporting
confidence: 94%
“…Cucarella and Renman (2009) emphasised that high solute concentrations encourage other adsorption mechanisms, such as substantial boundary concentrations; Zhang highlighted that the P adsorption of a filler is only attributed to the physical adsorption in low P concentration water, while the high P concentration of the water can sufficiently cause chemical reactions, such as complexation and precipitation, with the metals (Zhang et al 2005). In addition, some works have reported that the equilibrium adsorption capacity of aerated concrete for phosphorus reaches 300-6064 mg/kg, which is much higher than the amount of the P adsorption obtained in the present study (Fu & Li 2011;Deng & Wheatley 2018;Zhang & Zhu 2018;Castellar et al 2019). The results of the above studies were mainly due to them being based on kinetic bath studies of aerated concrete, which was crushed into a powder and then placed in extremely high P concentration water (5-60 mg/L), and the gained equilibrium adsorption capacity was nearly the theoretical maximum.…”
Section: Resultscontrasting
confidence: 71%
“…Few studies have shown the potential of using recycled material for structure of green walls such as polyethylene modules [25], recycled PET bottles [26], or cork boards [27]. Nowadays, there is also a great variety of waste materials being tested and validated in terms of their performance to be used as filter media in NBS: cork [28], coconut shell [23], recycled glass beads [29], mix of coir fibber and perlite [30], and crushed autoclaved aerated concrete [31]. One can conclude that creating new applications to waste materials is the basis for the establishment of an integrative urban chain, where the demand for manufactured products and disposal of waste is reduced.…”
Section: Contribution Of Nature-based Solutions Towards Circularitymentioning
confidence: 99%
“…Bê tông là sự kết hợp của cốt liệu gồm sỏi hoặc đá kết hợp với cát và xi măng. Các nghiên cứu đã sử dụng các phương pháp: nhiễu xạ tia X (X-ray diffraction-XRD), kính hiển vi điện tử quét (scanning electron microscopy-SEM) và phân tích phân tán năng lượng tia X (energy-dispersive X-ray analyses-EDX), phân tích diện tích bề mặt, độ rỗng xốp Brunauer -Emmett -Teller (BET) để xác định thành phần hóa học và đặc tính kỹ thuật của bê tông phế thải [6][7][8][9][10][11][12][13][14][15][16][17]. Thành phần các nguyên tố theo khối lượng (%) của bê tông phế thải đã được Nasreen và cs.…”
Section: đặC Tính Kỹ Thuật Một Số Loại Bê Tông Phế Thảiunclassified